Evaluation of the Nature of Armed Violence and Security Intervention in Benue State, Nigeria - Iornumbe, D.A. PhD; Liman Abdullahi Nuhu; Andrew Zamani (Jurnal Restorasi : Hukum dan Politik, 2025)
This article evaluates the nature of armed violence and security intervention in Benue State, Nigeria. Benue State has experienced a surge in armed violence in recent years, leading to a significant threat to human security, peace, and development. Although all levels of government have taken a number of strategically significant steps to end the violence/conflict, including the deployment of security agencies to coordinate in a way that could result in a joint force operation to end the conflict and restore peace and stability. The armed violence in Benue State continues to be a major source of concern for the local and international community, as well as an existential threat to the indigenous population. However, the results of the security intervention are tainted with conflicting reports of success and numerous obstacles that outweigh the successes attained. Based on the extensive literature review, it is clear that the security agencies had a great deal of success in combating the armed conflict's perpetrators; however, much remains to be desired because the situation in Benue State is getting worse despite the military and other security agencies' continued presence. The study reveals that the armed violence is complex and multifaceted, perpetrated by various groups, including herders, farmers, and militant groups. The security intervention measures implemented by the Nigerian government have been inadequate and ineffective, and have been criticized for being partisan and biased. With an unwavering commitment to ending the war, the government and key stakeholders must work together to develop more innovative methods and strategies for implementation. This article recommends the establishment of an independent commission to investigate the armed violence, the establishment of a trust fund to support victims, and the reform of the security agencies to ensure impartiality and effectiveness. The research used secondary data. Frustration aggression and system theories were used.